Neuroblastoma cells contain a trophic factor sharing biological and molecular properties with ciliary neurotrophic factor. - Heymanns, J (1987)
Ciliary neurotrophic factor (CNTF) is a protein supporting the in vitro survival of a characteristic spectrum of embryonic chicken and rat peripheral neurons. High-speed supernatants of extracts from two neuroblastoma (NB) cell lines--the mouse C 1300 N2a and the human IMR 32--mimic the effects of CNTF on identical target neurons. Promotion of survival is dose-dependent with an ED50 of 80 micrograms (IMR 32) and 140 micrograms (C 1300 N2a) of protein per ml and saturable at plateau values for surviving neurons identical to those achieved with purified CNTF. Small amounts of a CNTF-like material are also detectable in medium conditioned by NB cells. The activity is destroyed by heat and trypsin and not blocked by antibodies to (mouse) nerve growth factor. Unlike the neurite-promoting and neuronal-survival modulating agent laminin, it cannot be depleted on poly(L-alpha-ornithine)-coated plastic surfaces. NB IMR 32 cell extracts were electrophoresed using NaDodSO4/PAGE and transferred to nitrocellulose. Ciliary ganglion neurons seeded on the blotting paper in culture medium lacking CNTF ("cell blot") exclusively survive on two distinct bands with apparent molecular masses of 24 and 48 kDa. Twenty-four kilodaltons is the molecular mass of a CNTF purified from rat sciatic nerve. These results suggest that NB cells may contain a CNTF-like protein and provide further evidence that neurons may store neurotrophic factors. Purified (chicken) CNTF failed to affect proliferation and neurite growth of NB cells. The biological relevance of CNTF for NB cells, therefore, remains to be elucidated.